Treasures of Britain : The Architectural, Cultural, Historical and Natural Heritage of Britain - Edited by Norwich, John Julius, 1929- (Hampshire Everyman Publisher, 2005)
This comprehensive guide covers Britain's best architecture, art and natural beauty, from castles and historic houses, abbeys and cathedrals to beautiful villages, museums and art collections. It includes an introduction to the history, literature, art and architecture of Britain
Include Color Illustration and Map
Keywords: Great Britain -- Historic buildings -- Historic sites